Internal Factors within Entrepreneurs that Influence the Acceptance and Use of Social Commerce among SMEs in Malaysia - Azilahwati Binti Adam; Jessnor Elmy Binti Mat Jizat; Mohd Asri Bin Mohd Nor (Universitas Pelita Harapan, 2016)
Current technological advances, particularly in information and communications technology (ICT) and social media have sparked a phenomenon in the business world. The existence of social commerce (s-commerce), which is a combination of e-commerce and social media, has opened up greater opportunities for SMEs in Malaysia. The use of s-commerce as a medium for marketing and buying and selling is capable of helping SMEs to increase the sales and profitability of their businesses. However, according to studies conducted by SME Corp Malaysia, the usage of e-commerce and social media is still low. Attitude and self-efficacy are variables that are often used in studies related to entrepreneurs and their intention to accept a new business innovation or technology. Therefore, this study was undertaken to identify the internal factors within entrepreneurs, namely attitude and self-efficacy, which influence the acceptance and use of s-commerce among SMEs in Malaysia.